Tuning and in situ monitoring of surface-initiated, atom-transfer radical polymerization of acrylamide derivatives in water-based solvents. Issue 29 (3rd July 2019) - Mandal, Joydeb; Simic, Rok; Spencer, Nicholas D.
Abstract : SI-ATRP kinetics of acrylamide derivatives is studied in situ using a quartz crystal microbalance with dissipation (QCM-D). The effect of growth kinetics on polymer-brush dispersity have been examined using colloidal-probe atomic force microscopy. Abstract : In order to gain better control over the growth and dispersity of surface-tethered poly(acrylamides), the SI-ATRP kinetics of N -isopropylacrylamide (NIPAM), N, N -dimethylacrylamide (DMAM) and N -hydroxyethyl acrylamide (HEAM) have been systematically investigated in situ in an 80 : 20 ethanol/water mixture by means of the quartz crystal microbalance with dissipation (QCM-D). The addition of tetraethylammonium chloride (tEtAmCl) or tetraethylammonium bromide (tEtAmBr) in association with additional Cu II X2 (X = Cl or Br) resulted in improved control over the polymerization kinetics. Evidence for such improved SI-ATRP kinetics was provided by a slower and more linear decrease in the resonance frequency of the QCM-D sensors, indicating a linear increase in solvated brush mass as a function of polymerization time. This was further validated by carrying out multiple re-initiations and measuring the growth of the polymer brushes upon each initiation, by means of both QCM-D and ellipsometry. An indirect estimation of the effect of improving the living nature of polymer brush growth on their dispersity was performed by carrying out nanoindentation experiments by means of colloidal-probe atomic force microscopy on polymer brushes grown under different reaction conditions. For an identical indentation load, polymer brushes grown in the absence of Cu II X2 and tEtAmX exhibited a much larger indentation depth, indicating a substantially softer structure, presumably as a consequence of the higher degree of chain-length dispersity.